Production and characterization of collagen and gelatin from edible jellyfish (Acromitus hardenbergi Stiasny, 1934) for fabrication of biofunctional scaffold - Khong, Nicholas Mun Hoe (2014)
Jellyfish have always been an important fishery commodity and a multi-million business widely practised in China, Japan, Malaysia, Indonesia, Thailand, Vietnam and the Philippines. This study aimed to explore food and nutritional properties of indigenous jellyfishes; which contributes to the development of simple and efficient extraction procedures of jellyfish collagen and gelatin that would be practical in the production of biomedical-significant matrices for potential tissue engineering applications. It was found that edible jellyfishes were food of low calorific value (ranged from 1.0 to 4.9 kcal/g dry weight) and high protein (ranged from 20.0 to 53.9 g/ 100g dry weight) and minerals (total ash ranged from 15.9 to 57.2 g/ 100g dry weight) components. Collagen was estimated to comprise approximately half the total protein content of edible jellyfishes, hence the major protein component of edible jellyfishes. Among the jellyfishes, A. hardenbergi exhibited significantly (p < 0.05) better protein quality (higher total amino acids and collagen content) and richer in major minerals compared to other two species. Subsequently, two novel procedures were devised for efficient collagen and gelatin extraction from A. hardenbergi. It was found that this improved process significantly increased the production yield (p < 0.05) by approximately seven times and two times compared to the conventional acid-assisted and pepsin-assisted extraction, respectively. Proximate composition and amino acids profile of collagen extracted using the improved process was found to be similar (p > 0.05) to those extracted using the pepsinassisted extraction. However, the collagen produced by the improved process retained high molecular weight distributions and polypeptide profiles similar to the conventional acid-assisted extraction. They possessed better appearance,instrumental colour and were found to be non-toxic in vitro and free of heavy metal contaminations. Findings from comparisons between the novel and the conventional procedures illustrated that different treatments of collagen extraction process imparts significant impacts to the quality, quantity and cost of the collagen produced. The study also managed to extract gelatin successfully from jellyfish tissues with satisfactory yield, gelling (Bloom) and sensory properties. Jellyfish gelatin has high protein content (>80%) with low moisture (<2.5%), ash (<2.0%) and negligible fat contents. All gelatins had very mild to undetectable fishy odour and were all whitish in appearance. Jellyfish collagen and gelatin were then used to fabricate porous scaffolds suitable for tissue engineering application by freeze-drying the mixture with different proportions of chitosan solutions. The addition of jellyfish gelatin into the scaffold formulation, to partially substitute collagen, was able to reduce the production cost while improving functional characteristics of the scaffolds. The combinations of different jellyfish collagen and gelatin concentrations were observed to have significant effects on the cross-section morphology and the molecular integrity of the cross-linked scaffolds. Proportional combination of jellyfish collagen into the ternary scaffolds was found to significantly (p < 0.05) increase mean pore size and porosity. All ternary scaffolds exhibited mean pore size in the range of 200-300 μm and porosity above 90%. These results suggested that the chitosan: jellyfishderived collagen and gelatin tripolymer matrix is a potential candidate for soft tissues equivalent with enhanced biostability and good biocompatibility. Overall, the findings of this study supported that jellyfish is potentially practical as a sustainable source of high quality collagen and gelatin. Jellyfish-derived biomaterials were also found to exhibits good biophysicofunctionality in the fabrication of scaffolds for tissue engineering. Scaffolds, fabricated in the current study is but a beginning for more forms of functional matrices such as hydrogel, sol, liquid, concentrate and powder.